KUALITAS FISIK DAGING SAPI YANG DILAYUKAN SECARA TRADISIONAL - POETY M. K.; N. L. P. SRIYANI; A. A. OKA (Fakultas Peternakan Universitas Udayana, 2021)
This research aims to determine the effect of traditional aging meat on the physical quality of beef and the opti- mal time of traditional withering to obtain good quality beef. The research material used was beef on the LD muscle (Longisimus dorsi). The design used was completely randomized design (CRD) with 4 treatments and 4 replicati- ons, namely P0 = fresh meat without aging, P1 aging beef for 6 hours, P2 aging beef for 8 hours and P3 aging beef for 10 hours at room temperature 28-29oC. The variables observed in this study were pH, color, water holding capacity, cooking losses, and weep lose. The results showed that statistically traditional aging beef was significantly different (P<0.05) on the pH value, color and weep lose but not significantly different (P>0.05) on the value of water holding capacity and cooking loss. It can be concluded that the length time of aging beef could affect beef physical quality and the optimal time to produce the best quality physic of the beef is 6 hours.